Prototipe Light Meter Fotografi Studio Menggunakan Mikrokontroler ATMega328 Berbasis Sensor Cahaya dan Warna - Chairul Gunawan; Fauziah Fauziah; Nur Hayati (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Accuracy in calculating exposure in photographic techniques is the key to being able to produce good quality photos. The light calculation includes three elements (Triangel Exposure), namely shutter speed (shutter speed / t), ISO sensitivity, and diaphragm (aperture / f). A light meter is a tool for calculating lighting in the world of photography to accurately calculate the light falling in or around the object to be photographed. The light meter has a working principle like a lux meter calculates the value of light intensity in a place. However, on a light meter for photography, there is a calculation of a triangle exposure in it. This light meter prototype uses an ATMega328 microcontroller on the Arduino Nano V3 with the help of a TSL2561 light sensor and a TCS34725 RGB color sensor. Tests were carried out by comparing the output value using an original light meter, namely Sekonik Flashmate L-308X with the continuous light shooting method. The results of the test using the original tool with the ATMega328 microcontroller produced values above 90%.